Schneiderian symptoms and DSM 5: related to two cases - HİCRİ, NURŞİN; YANARTAŞ, ÖMER; ERGÜN, SERHAT; GÜRSOY, SÜHA CAN (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2017)
Thought to be more common in psychotic disorders in the past, Schneiderian symptoms (SS) were also observed in other disorders such as dissociative disorders and bipolar disorders. As a result of this, specific attribution of Schneiderian first rank symptoms was eliminated from diagnostic criteria of schizophrenia in DSM-5. In this article, we aim to present two cases having schneiderian symptoms. Since these cases had additional symptoms such as amnesia, fugue, and Schneiderian symptoms related to psychosocial stressors, we also suggested that these patients might have dissociative disorders. In terms of Schneiderian symptoms; instead of antipsychotic treatments, psychotherapeutic interventions and removal from psychogenic stressors can be considered in management of these cases. In DSM-5 the elimination of specific attribution of SS in psychosis results in clinician's drawn attention to this issue in other disorders. Therefore, this alteration may provide better diagnosis of dissociative disorders and bipolar disorders and prevent these patients' from taking high dose antipsychotic treatments unnecessarily.
Keywords: schneiderian symptoms; schizophrenia; dissociative disorders; bipolar disorders; DISSOCIATIVE IDENTITY DISORDER; MULTIPLE PERSONALITY-DISORDER; 1ST RANK SYMPTOMS; 1ST-RANK SYMPTOMS; CHILDHOOD TRAUMA; SCHIZOPHRENIA